Computer game playing habits of children at pre-school education level by their families’ views - Aydın, Diler; Yıldız, Suzan (Journal of Dependence, 2016)
Objective: This study aims to examine the computer game-playing habits of children at preschool education level from the point of view of their families.Method: The research was structured as descriptive study. The study of the population was based on 410 children attending 6 kindergartens in a district of Balikesir province; and the sample is based on 321 children and their families. Data were collected with face-to-face interview method with a questionnaire form developed by researchers. The data were evaluated with SPSS 19.0 statistical package program using number-percentage distribution, chi-square test and logistic regression.Results: 80.7% of participating children were found to play computer games. No significant difference was found between children’s game-playing (playing versus not-playing) and either age range or gender (p>0.05). A positive significant relationship was found between children’s game-playing habits and those of their families through logistic regression evaluation (p
Keywords: Child; computer games; preschool; parenting